Positive and Negative Sentiment of Artificial Intelligence in Language: Study Prompt on Chat GPT - Wildan, M (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
The study explored both positive and negative sentiments towards artificial intelligence in language, focusing on study prompts using Chat GPT. The goal of this study is to understand how users perceive and judge AI in the context of language models such as Chat GPT. The research method used is qualitative descriptive, which focuses on prompts aimed at bringing up language facts. Data collection is carried out through a prompt submission which is then responded to by Chat GPT. Data analysis was carried out using a narrative analysis approach. It is intended to identify patterns of positive and negative sentiment in the responses given by Chat GPT. The results of the study showed that there was a Chat GPT response that led to positive and negative sentiment. The prompts "mohon" and "apakah" are some of the prompts that contain positive elements. The absence of these two prompts is an element in Chat GPT that leads to negative sentiment. The implications of this research are to provide insights for AI developers to improve the quality and acceptance of AI technologies in the future, as well as address existing concerns regarding privacy and accuracy.